Rattus feliceus Thomas 1920 - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Rattus feliceus Thomas, 1920. Ann. Mag. Nat. Hist., ser. 9, 6:423. TYPE LOCALITY: Indonesia, Kepulauan Maluku, Pulau Seram, Gunung Manusela, 6000 ft. DISTRIBUTION: Known only from Seram Isl. COMMENTS: An amplified description and comparison with R. koopmani from Peleng Isl were provided by Musser and Holden (1991), who also discussed past, and incorrect, subspecific allocations of feliceus to other species of Rattus. Phylogenetic affinities of R. feliceus are with species of Rattus endemic to New Guinea region (Musser and Holden, 1991). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 652, DOI: 10.5281/zenodo.7353098